Effect of immunocastration and housing conditions on pig carcass and meat quality traits. Issue 2 (6th May 2020) - Škrlep, Martin; Poklukar, Klavdija; Kress, Kevin; Vrecl, Milka; Fazarinc, Gregor; Batorek Lukač, Nina; Weiler, Ulrike; Stefanski, Volker; Čandek-Potokar, Marjeta
Abstract: The present study investigated the effects of immunocastration and housing conditions on carcass, meat, and fat quality traits. Immunocastrates (IC, n = 48), entire (EM, n = 48), and surgical castrates (SC, n = 48) male pigs were reared under three different housing conditions. The conditions were standard ( n = 36), enriched ( n = 36, twice as much space as standard and additional outdoor access), or standard with repeated social mixing ( n = 72). Pigs of the IC group were vaccinated at the age of 12 and 22 wk. The animals were slaughtered in four batches, balanced for sex category and housing, at the age of 27 wk reaching 124.7 ± 1.0 kg. Immunocastration led to increased fat deposition (i.e., thicker subcutaneous fat at different anatomical locations, more leaf fat, fatter belly in IC than EM, P < 0.05) but did not affect muscularity traits. As a result, EM exhibited higher and SC lower ( P < 0.05) carcass leanness than IC. Fatty acids composition of either subcutaneous or intramuscular fat (IMF) agreed with general adiposity, that is, IC were intermediate between EM and SC exhibiting the lowest and highest fat saturation ( P < 0.05), respectively. Compared to SC, EM exhibited higher ( P < 0.05) levels of muscle oxidation and collagen content than SC, with IC taking an intermediate position in the case of the level of peroxidation and collagen content, or closer to SC as regards to oxidation of muscle proteins (i.e., carbonyl groups). Meat quality (including marbling score, cooking loss, subjective color redness, and chroma) of IC was similar to EM, and both differed ( P < 0.05) from SC. However, IC and SC had less ( P < 0.05) tough meat than EM, consistent with protein oxidation. The effect of housing was less evident. Mixing of pigs resulted in lower ( P < 0.05) carcass weight and fatness in all sex categories with lower ( P < 0.05) oleic and higher (P < 0.05) arachidonic acid in IMF of EM.